Euro-Par 2006 workshops [electronic resource]: parallel processing : CoreGRID 2006, UNICORE Summit 2006, Petascale Computational Biology and Bioinformatics, Dresden, Germany, August 29-September 1, 2006 : revised selected papers - International EURO-PAR Conference (12th 2006 : Dresden, Germany); Lehner, Wolfgang, 1969-; SpringerLink (Online service) (Berlin, Heidelberg : Springer-Verlag Berlin Heidelberg, 2007)
41